TINDAK PIDANA JUAL BELI GAME ONLINE DI MASA PANDEMI - Nurhotia Harahap (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2020)
Online games are now increasingly popular and are widely played by various groups. Marketing Director of SEA PUBG Mobile, Oliver Ye stated that Indonesia is in the second position of active PUBG players at the international level. WHO has also included gaming disorder in the 11th Revision of the International Classification of Diseases (ICD-11). From a health aspect, online gaming causes a decrease in front brain waves which results in decreased ability to control emotions. So that it will cause mood changes quickly, irritability, difficulty concentrating, damage the eyes, and so on. Even economically, online games have the potential to plunge players into bankruptcy. It is not uncommon for a fractured household to lead to divorce as a threat.